Synergetic Effect of Combined CaO2 and Microwave Treatment on Waste Active Sludge Dewaterability and Organic Contaminants’ Removal - Wang, Jie; Shang, Kankan; Da, Liangjun; Liu, Xingguo; Zhao, Yongjing; Zhang, Ai (Frontiers in Environmental Science, 2021)
This study investigated the synergetic effect of the combined calcium peroxide (CaO2) and microwave (MW) treatment on waste active sludge dewatering properties and organic contaminants removal. The optimal sludge dewaterability was obtained at CaO2 (20 mg/gVSS)/MW (70 oC), and the capillary suction time decreased by 52% compared with raw sludge. Further investigation indicated that total extracellular polymeric substances (EPS), tightly bound EPS, total protein and protein present in tightly bound EPS were closely correlated with sludge dewaterability. Tryptophan, aromatic proteins-like substances and humic acid-like substances were the key compounds that affect sludge dewaterability. The charge neutralization and bridge effect of cations ions were strengthened when combined with MW irradiation. In addition, it was revealed that MW facilitate CaO2 to produce more hydroxyl and superoxide anion radicals. This study confirmed that CaO2/MW to be a effective way to improve sludge dewatering and remove organic pollutants from sludge.